2010
DOI: 10.3344/kjp.2010.23.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Air Bubbles Mimic Disc Herniation in MRI after Cervical Epidural Block

Abstract: Magnetic resonance image (MRI) is the most sensitive imaging test of the spine in routine clinical practice. Unlike conventional x-ray examinations and computed tomography scans, high-quality magnetic resonance images can be assured only if patients are able to remain perfectly still. However, some patients find it uncomfortable to remain still because of pain. In that condition, interlaminar cervical epidural injections can reduce pain and allow the procedure. When using air with the "loss of resistance" tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…There were 36 cases related to pain management complications or adverse events. Although they included contents related to pain procedures, including drug allergy and diagnosis issues [ 23 24 25 ], they only examined extremely rare cases for academic purposes. Therefore, these cases are not applicable to practical law issues affecting pain physicians.…”
Section: Discussionmentioning
confidence: 99%
“…There were 36 cases related to pain management complications or adverse events. Although they included contents related to pain procedures, including drug allergy and diagnosis issues [ 23 24 25 ], they only examined extremely rare cases for academic purposes. Therefore, these cases are not applicable to practical law issues affecting pain physicians.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that air bubbles collect near the outlet space for the exiting nerve roots. Therefore, while a large amount of air injection may cause radiculopathy, even the smallest amount of air may show up on an MRI as a herniated disc [13]. …”
Section: Discussionmentioning
confidence: 99%
“…In patients receiving an ESI for treatment of spinal diseases, there is a possibility of misreading or difficulty in interpretation of MR images because of air or fluid in the epidural space after the injection. Kim et al [ 7 ] reported a case of air bubbles mimicking disc herniation in MR images acquired after a cervical epidural block. Additionally, Ammirati and Perino [ 8 ] reported a case of symptomatic epidural air trapped in the spine after ESI.…”
Section: Introductionmentioning
confidence: 99%